2013
DOI: 10.1039/c3nr01836a
|View full text |Cite
|
Sign up to set email alerts
|

Logical regulation of the enzyme-like activity of gold nanoparticles by using heavy metal ions

Abstract: In this study we employed self-deposition and competitive or synergistic interactions between metal ions and gold nanoparticles (Au NPs) to develop OR, AND, INHIBIT, and XOR logic gates through regulation of the enzyme-like activity of Au NPs. In the presence of various metal ions (Ag(+), Bi(3+), Pb(2+), Pt(4+), and Hg(2+)), we found that Au NPs (13 nm) exhibited peroxidase-, oxidase-, or catalase-like activity. After Ag(+), Bi(3+), or Pb(2+) ions had been deposited on the Au NPs, the particles displayed stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 82 publications
3
77
0
Order By: Relevance
“…Lead interferes with the development of the nervous system and is particularly toxic to children, causing potentially permanent learning and behavior disorders. [6][7][8][9][10][11] Metal nanoparticles have attracted particular interest in the detection of Pb 2+ owing to their unique electronic, magnetic, catalytic and optical properties, which are different from bulk metals and dependent on their size and shape. No safe threshold for lead exposure has been discovered, i.e., there is no known sufficiently small amount of lead that will not cause harm to the body.…”
Section: Introductionmentioning
confidence: 99%
“…Lead interferes with the development of the nervous system and is particularly toxic to children, causing potentially permanent learning and behavior disorders. [6][7][8][9][10][11] Metal nanoparticles have attracted particular interest in the detection of Pb 2+ owing to their unique electronic, magnetic, catalytic and optical properties, which are different from bulk metals and dependent on their size and shape. No safe threshold for lead exposure has been discovered, i.e., there is no known sufficiently small amount of lead that will not cause harm to the body.…”
Section: Introductionmentioning
confidence: 99%
“…Pt(IV) ions were directly reduced to PtNPs and PtNPs were anchored to the GO surface mainly through the oxygen functional groups of GO and protein. After the addition of Bi 3+ , strong metallophilic interactions (between Pt and Bi) or the electrostatic attraction (between Bi 3+ and protein) resulted in deposition of Bi 3+ on the PtNP surfaces . Previous studies have demonstrated that polymers might preferentially adsorb on some specific facets of inorganic nanocrystals, resulting in oriented attachment and formation of anisotropic nanostructures .…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27] Typically, MLDs are not like semiconductor-based logic in employing voltages as the input/output (I/O) signals, but instead use chemical or biochemical inputs and electrochemical [28][29][30] or spectroscopic/photonic outputs. 16,20,22,23,[31][32][33][35][36][37][38][39][40][41] By virtue of dipole-dipole coupling between their component molecules, photonic-based MLDs oen support shortrange (<10 nm) internal communication via Förster resonance energy transfer (FRET) which opens up fruitful avenues for logic gate design. Thus, MLDs have been hindered in terms of inherent complexity and function.…”
Section: Introductionmentioning
confidence: 99%